THE VALUE OF FIGHTING DANCE TO AVOID CULTURAL VIOLENCE PERSPECTIVE: ON CACI OF THE MANGGARAI TRIBE - Maria Paskalia Aninda; Lambok Hermanto Sihombing (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
This article discusses the traditional fighting dance widely known as Caci. Caci still exists in the Manggarai tribe East Nusa Tenggara, a sacred ceremony and contains a moral message value. In this study, we will examine how the value of Caci reduces the perspective of Violence. The data comes from YouTube about the Caci in Manggarai and interviews with an informant. This study used the structuration theory proposed by Anthony Giddens. Based on the results is behind the Caci performance, which is so aggressive, the iconic its uniqueness has an implied meaning about the relationship the humans with God. For the Manggarai tribe, being physically injured in Caci is a natural thing to happen and doesn't count as violent or fighting with opponents.